Kesesuaian Lahan Sawah Pasang Surut dan Faktor Pembatas Utama Tanaman Padi di Kecamatan Sinaboi, Kabupaten Rokan Hilir - Muntazar, Mhd Roqi; Nasrul, Besri; Wawan, Wawan; Idwar, Idwar; Khoiri, M Amrul; Silvina, Fetmi; Nurhayati, Nurhayati (Jurnal Pedontropika : Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2022)
The paddy production is decreasing due to land characteristics that are not suitable for its crop requirements. This study aims to identify the inhibiting factors of growth and production and evaluate land suitability based on the factors that inhibit growth and production of tidal paddy fields. The research method used is a soil survey. Soil sampling points were determined based on the overlay results of the current paddy field map and the map of land and soil units. The suitability assessment of paddy fields is carried out using a matching system in actual and potential conditions. The actual land suitability of all SLH is not current suitable (N1) with a very high Fe inhibiting factor. Limiting factors of Fe content can be overcome by making one-way drainage channels, adding organic matter, liming, fertilizing and or using tolerant varieties. The potential land suitability of all SLH is marginally suitable (S3).